2010
DOI: 10.1371/journal.pone.0015510
|View full text |Cite
|
Sign up to set email alerts
|

Transmitted Drug Resistance in Persons with Acute/Early HIV-1 in San Francisco, 2002-2009

Abstract: BackgroundTransmitted HIV-1 drug resistance (TDR) is an ongoing public health problem, representing 10–20% of new HIV infections in many geographic areas. TDR usually arises from two main sources: individuals on antiretroviral therapy (ART) who are failing to achieve virologic suppression, and individuals who acquired TDR and transmit it while still ART-naïve. TDR rates can be impacted when novel antiretroviral medications are introduced that allow for greater virologic suppression of source patients. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 27 publications
3
58
0
Order By: Relevance
“…As PIs use in the US was much more popular than NNRTIs, TDR related to the NRTIs and NNRTIs are more common as compared to TDR related to PIs, which is consistent with other studies [4,10,11].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As PIs use in the US was much more popular than NNRTIs, TDR related to the NRTIs and NNRTIs are more common as compared to TDR related to PIs, which is consistent with other studies [4,10,11].…”
Section: Discussionsupporting
confidence: 91%
“…There are two important sources of TDR: (1) persons who develop drug resistance mutations while on ART and subsequently transmit HIV and (2) persons who acquire TDR mutations during initial infection and maintain the mutations in the absence of ART until they transmit HIV [4]. If TDR trends are driven primarily by persons with drug-resistant HIV who are viremic despite taking ART, changes in ART can help achieve better suppression of drug resistance and rapidly decrease TDR rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, the transmission of drug-resistant viruses, which can sometimes persist even without the selective pressure of HAART, was becoming increasingly frequent (9,20). Nowadays, several studies show a decline in the transmission of drug-resistant variants in the western world to approximately 10% (2,14), whereas other studies still report stable transmission rates for certain resistance-associated mutations (RAMs) (5,45). The key to an effective treatment regimen relies on both the genetic barrier to resistance to a specific drug and on the ability of antiviral drugs to decrease viral load.…”
mentioning
confidence: 99%
“…Recent large populationbased studies in the United States, Africa, and Europe have found TDR rates in the range of 6%-16%, with higher levels of resistance in certain urban populations, particularly those who engage in high-risk sex and intravenous drug users (Table 2). [101][102][103][104][105][106][107][108][109][110] In a study of 1277 newly infected patients with HIV-1 in South Carolina, 184 (14%) had TDR. 54 (4%) had an NRTI mutation, 37 (3%) had a PI mutation, and 126 (10%) had an NNRTI mutation.…”
Section: Resistancementioning
confidence: 99%